Analysis of Phosphate Content of Cola Drinks and an Attempt to Estimate the Phosphate Intake with These Drinks by Young Adults – A Pilot Study - Haraf, Gabriela; Dziurbiel, Jan (Analiza zawartości fosforanów w napojach typu cola i próba oszacowania spożycia fosforanów z tymi napojami przez młodych dorosłych – badanie pilotażowe, 2025)
Aim: This study was designed as a pilot to determine the orthophosphate (PO43) content of cola drinks available in Poland on the Wrocław market, attempt to estimate the amount of phosphorus (P) in soft drinks consumed by young adults (18-35 years old) and examine their level of knowledge about sources of PO43in the diet and the potential harm of their excess. Methodology: The analysis of cola drinks was performed using Merck’s rapid reflectometer test. Asurvey was also conducted via the Google Forms platform. Results: The analysis of cola drinks showed that the PO43content varied from 125 to 875 mg/l. The survey showed that the respondents have limited knowledge of the harmfulness of excess P and its presence in food. Declared consumption of cola drinks ranged from 250 to 9,000 ml/week. Coca-Cola Zero and the classic Coca-Cola were the most frequently chosen beverages. The average P intake of young adults with these beverages amounted from 23 to 267 mg/day. Implications and recommendations: According to scientific reports, the stated daily intake of P should not cause health problems. Nevertheless, its daily intake should be monitored, especially for people with health issues such as kidney disease or hypoparathyroidism. Originality/value: Monitoring the PO43content in processed foods is important due to the increasing popularity of this type of food and the assessment of the health risks associated with excess P in diet.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2025, Nr 41, s. 1-12